Comparative evaluation of the depth of remineralization with casein phosphopeptide-amorphous calcium phosphate, sodium fluoride with CXP, nano-hydroxyapatite, and sodium fluoride on artificially demineralized lesions using stereomicroscope: An In vitro study - Gaurav Anand Rane; B Sandhyarani; Anil T Patil; Kunal Keshaw; Anita Raikar; Rucha Davalbhakta (Journal of Indian Association of Public Health Dentistry, 2023)
Aim: This study aims to know the efficacy of remineralization of four fluoride varnishes on artificial demineralized lesions in primary teeth. Materials and Methods: A total of 60 human primary anterior teeth coated with nail varnish leaving a window of 3 mm × 3 mm were subjected to demineralization for 72 h. These teeth were then sectioned into two equal parts with a diamond disc. These 60 sections obtained were then evaluated under the stereomicroscope and the demineralization depth was noted. These 60 sections were divided into four groups: Group 1: Casein phosphopeptide-amorphous calcium phosphate (CPP-ACP); Group 2: Sodium fluoride (NaF) with xylitol-coated calcium and phosphate (CXP); Group 3: Nano-hydroxyapatite; Group 4: NaF and subjected to remineralization respectively for 5 days. The specimens were again evaluated under the stereomicroscope for the remineralization depth. Results: All the four varnishes showed remineralization with artificial carious lesions. CPP-ACP showed the highest remineralization depth followed by NaF with CXP, NaF, and Nano-hydroxyapatite. Conclusion: CPP-ACP can be used as an agent at its best for remineralizing and extending the life of the tooth.